Experimental investigation of surface roughness effects on energy harvesting from a piezoelectric eel behind a cylindrical bluff body. - Muhammad Hammad Bucha; Niaz Bahadur Khan; Emad Uddin; Hafiz Hamza Riaz; Adnan Munir; Umar Farooq; Ming Zhao; Riaz Muhammad; Mohammed Jameel; Muhammad Tauseef Nasir; M Nafees Mumtaz Qadri (PLoS ONE, 2025)
Due to dwindling energy reserves and the cost-effectiveness of installation, the global trajectory is shifting towards renewable energy sources as a proficient means of energy acquisition. Among these sources, hydropower stands out as it harnesses the kinetic energy of oceanic water flow to generate power. Various studies have harnessed vortex-induced vibrations (VIV) to generate power from a piezoelectric eel, showcasing the diverse applications of this technology. The present experimental study further explores this technology and investigates the effect of surface roughness of cylindrical bluff body on the energy harvested by piezoelectric eel using a low-speed water tunnel. The experiments were performed at four different roughness values (Ks/D) namely 2.21, 4.07, 9.85, and 13.97 microns for the cylinders with diameters of 25, 27, 27.2, and 27.5 mm, respectively. The Reynolds number in the present study is fixed at 8690. A total of hundred case studies were performed to analyze the effect of the surface roughness of the cylinder on energy harvesting performance from the eel. The flapping frequency, amplitude, and optimal power of the rough cylinders were analyzed and compared with that of smooth cylinders experimentally, and the optimum point ([Formula: see text]) in terms of power was attained. Increased surface roughness significantly reduced power output, flapping frequency, and amplitude. The smoothest cylinder (Ks/D = [Formula: see text]) produced the highest power (52.325 µW), while the roughest (Ks/D = [Formula: see text]) resulted in a 6.26% decrease in power (36.4 µW), along with reductions of 4.5% in flapping frequency and 20% in amplitude. By increasing the surface roughness of the bluff body, the lock-in region decreases and as a result, the harvested power from that bluff body is reduced. Moreover, the power also decreased by increasing the distance between the cylinder and eel both in the x- and y-direction. The results of the current study provide deeper insights into the effect of surface roughness on energy harvesting from piezoelectric eel behind cylindrical bluff body, that are essential for the development of efficient energy harvesting systems. The findings of this study would be useful for the design of piezoelectric eel-based energy harvesting devices in marine environments.